ESTIMATIONS OF DYNAMIC PARAMETERS AND POSSIBLE HABITABLE ZONES FOR SELECTED STARS OF PULKOVO PROGRAM - Shakht, N. A.; Romanenko, L. G. (Одеські астрономічні публікації, 2013)
We give the results of a study of selected stars located in the neighborhood of the Sun. Their observations have been made by means of Pulkovo 26-inch refractor. An interest to these objects is raised in connection with expected results of the planned space missions.. We have made an estimation of habitable zones for possible planets rotating around of these stars.